Enhancing Vocational Teachers' Competence: A Cisco Packet Tracer-Based Simulation Model for Network Administration - Heriyanto, Heriyanto; Wulandari, Dian; Desianti, Lisa Chandrasari (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to improve teacher competence in network system administration subjects at vocational high schools by developing a Cisco Project Tracer-based simulation learning media and testing its feasibility, practicality, and effectiveness. This research employs the Research and Development method, adopting the ADDIE model. Quantitative data were analysed using a paired sample t-test and the N-Gain Score calculation. The expert validation results showed that the developed media achieved an average score of 89%, indicating